Siedlungssystem und Arbeitsmarkt - Einige empirische Resultate für die Bundesrepublik Deutschland - Bartels, Dietrich (ERDKUNDE, 1982)
With regard to the actual regional policies discussion of parameters influencing the employment in particular regions, the relationship between the employment within the tertiary sector of a region and the respective regional settlement structure, comparing the planning regions of the FRG on the 1970 data basis, will be analyzed here. The composition of settlement size classes and tertiary sector employment will be correlated within the frame work of two different models of spatial provision behaviour of a region’s population. As a result it will become apparent that (1) a model of distance-dependent behaviour of provision or substitution of needs has more explanatory power than the behavioural assumptions of a Christaller-model, and that (2) it seems justifiable to ascribe maximum employment effects within a region to the number of centres of medium size (about 80,000 inhabitants).